PENGEMBANGAN MEDIA KOMIK DIGITAL KOMPETENSI KELAINAN DAN PENYAKIT KULIT SISWA SMK LABSCHOOL UNESA 1 SURABAYA - Hasna' Atsilah Khashibah; Dewi Lutfiati; Dindy Sinta Megasari; Sri Dwiyanti (Program Studi Pendidikan Tata Rias, 2026)
Learning about skin disorders and diseases at SMK Labschool UNESA 1 Surabaya continues to face several challenges, including limited student interest in reading, heavy reliance on traditional learning media, and a lack of visual materials for topics that involve many scientific terms and lengthy explanations. The study’s main goal was to outline the creation of digital comic media, compare students’ learning outcomes before and after its implementation, and collect students' responses. A Research and Development (R&D) methodology was employed in the research, which was conducted over nine phases and utilised the Borg & Gall model. The sample consisted of 22 students from class X TKKR 2. Data was gathered using feasibility observation forms, pretest and posttest assessments, and student response surveys. Data analysis comprised descriptive quantitative methods, the Wilcoxon Signed Rank Test, alongside N-gain analysis. The digital comic media received an average feasibility score of 4.45, with material experts assigning 4,53, media experts 4,47, and language experts 4.10. Students’ learning outcomes demonstrated significant improvement, as indicated by a Wilcoxon p-value of 0.000 < 0.05, and supported by a N-gain score was 0.7002 (high level). Student responses also demonstrated as the questionnaire metrics reached an average score of 4.46 (highly feasible). In summary, digital comic media represents a highly feasible and effective approach for enhancing students’ learning outcomes and engagement.